Hammersmith Infant Neurological Examination asymmetry score detects hemiplegic Cerebral Palsy from typical development - Hay, Krystal (Pediatr Neurol, 2018)
BACKGROUND: The Hammersmith Infant Neurological Examination (HINE) is one of several useful tools for early identification of Cerebral Palsy (CP), however, cut-off scores for CP do not consistently distinguish infants with hemiplegia from those typically developing. We hypothesized that use of an asymmetry score, in addition to the assessment’s standard total cut-off score could remedy this problem in a clinical setting. METHODS: This retrospective study of a neonatal intensive care follow-up program with consistent clinical use of the HINE matched infants with a diagnosis of CP to infants without motor delays or evidence of neurodevelopmental impairments. Groups had same corrected and gestational ages at HINE assessment. Asymmetry presence was recorded. RESULTS: Of 74 infants with CP, 28 had quadriplegia, 11 had diplegia and 35 had hemiplegia. Median total HINE and asymmetry scores for hemiplegia were 57.5 and 10 vs. 76 and 0 for those without CP. Sensitivity and specificity to distinguish hemiplegia from typical development by combining a total HINE score <63 and an asymmetry score >5 were 91.8 and 100% respectively. CONCLUSION: In a clinical setting, combining total HINE and asymmetry scores can help providers differentiate infants with hemiplegia from those typically developing.